Fenomena Pergelaran Seni Pertunjukan Era Media Baru Sebagai Roll Model Pembelajaran Seni Budaya Di Sman 5 Kota Bukittinggi - Handayani, Lucy (CV. ITTC INDONESIA, 2022)
This study aims to discuss the development of digitalization planning (design) learning models in the subject of Cultural Arts in the New Media Era in class XII at SMA Negeri 5 Bukittinggi. This learning model was developed due to the conditions of the Covid-19 pandemic which required all learning processes at SMA Negri 5 Bukittinggi to be carried out online. This policy raises problems in learning materials in the field of performing arts practices which require students to learn art practices in class. The method used is the Zoom and YouTube applications as connecting media in connecting material from teachers (writers) to students and between students' performing arts creations and the wider community who will watch the performing arts. The results of this study can be of benefit to the public by analyzing every phenomenon that occurs in the world of education in the New Media Era, and as input or a roll model for arts and culture teachers at SMAN 5 Bukittinggi to be able to improve learning outcomes so that students are more active and enthusiastic in learning arts and culture .